Development of uptake assays for proton-coupled nutrient transporters - Josi Steinke (2022)
A wide range of membrane transporters play an essential role in providing cells with nutrients, maintaining cell homeostasis and mediating signaling processes. Since they were found to contribute in certain diseases and are able to transport selected drug molecules, many transporters were studied with the aim to gain knowledge about the transport mechanisms. Aside from the determination of the protein structure, functional assays provide a valuable tool for transporter characterization. The presented study focused on using label-free functional assays to detect substrate uptake into proteoliposomes driven by proton-coupled membrane transporters. For this purpose, the di- and tripeptide transporter DtpB from E. coli was used, which is a member of the Major Facilitator Superfamily. DtpB co-transports protons to drive uptake of small peptides against their concentration gradient. This proton-coupling was used in the functional assays shown here, by directly measuring proton-influx as a result of substrate translocation. The first assay established for DtpB was based on incorporating the pH-sensitive fluorescent dye pyranine into proteoliposomes and measuring the decrease in fluorescence upon proton-influx. Here, a charge-gradient was applied across the liposomal membrane to facilitate proton-coupled transport. A range of di- and tripeptides was screened for uptake by DtpB using this assay and 11 apparent substrates as well as one peptide with an inhibiting effect were identified. The collected transport data were further plotted against the respective KD values, which were determined for each peptide by nanoDSF (low volume differential intrinsic tryptophan scanning fluorimetry), to investigate the correlation between affinity and transport activity. This analysis showed that apparent substrates of DtpB clustered in the affinity range of 0.1 mM ≤ KD ≤ 4 mM and for most peptides outside this range no transporter mediated proton-influx was measured. Furthermore, the pyranine-based assay was also established for the Anion:Cation symporters LgoT and DgoT, as previously shown by Bartels (2020) and Leano et al. (2019), to further verify the assay and stereospecificity of both transporters was shown. Also, the KD and Vmax values were determined for selected substrates of all three transporters. The second uptake assay used here was a Solid Supported Membrane approach from the company Nanion, where proteoliposomes were attached onto a lipid bilayer on a gold coated sensor. Electrodes measured proton-flux into the liposomes as a change in current due to capacitive coupling of the liposomes to the sensor. With this assay, the transport of selected substrates identified in the pyranine-based assay was verified in absence of a membrane potential. In the frame of the presented work, both assays were shown to reliably detect transporter mediated proton-uptake and allow screening of a large number of compounds.